Influence of brand experience, customer review and customer satisfaction on repurchase intention among erigo customers on shopee - Bhangkit Febryhardo; Titin Ekowati; Dedi Runanto (International Journal of Applied Finance and Business Studies, 2026)
This study aims to analyze the influence of brand experience, customer reviews, and customer satisfaction on repurchase intention among Erigo customers on the Shopee marketplace. The research adopts a quantitative approach using a survey method, with a sample of 120 respondents who have previously purchased Erigo products through Shopee. The variables examined include brand experience (sensory, emotional, intellectual, and behavioral), customer reviews (argument quality, volume, valence, timeliness, and source credibility), customer satisfaction (expectation confirmation, willingness to repurchase, and willingness to recommend), and repurchase intention (transactional, explorative, preferential, and referential interest). Data were analyzed using multiple linear regression with SPSS 25.0, and all measurement instruments met validity and reliability requirements, with Cronbach’s alpha values exceeding 0.70. The results indicate that brand experience has a positive and significant effect on repurchase intention (β = 0.283, p < 0.001). Customer reviews also have a positive and significant influence on repurchase intention (β = 0.217, p < 0.001), suggesting that credible and positive reviews strengthen consumer confidence. Customer satisfaction is identified as the most influential variable (β = 0.327, p < 0.001), demonstrating that fulfilled expectations and positive consumption experiences strongly encourage repeat purchases of Erigo products. Theoretically, this study contributes to consumer behavior literature by confirming the role of experiential, informational, and affective factors in shaping repurchase intention in e-commerce contexts. Practically, the findings highlight the importance for Erigo and similar fashion brands to maintain consistent brand experiences, encourage authentic customer reviews, and enhance satisfaction drivers such as product quality, service responsiveness, and delivery accuracy.